The Influence of Leadership and the Role of School Committees on Teacher’s Performance - Iskandar, Eddy; Lian, Bukman; Mahasir, Mahasir (Journal of Social Work and Science Education, 2024)
The goal of this study was to evaluate the leadership of the principal and the function of the school committee at SMP Negeri 1 Pangkalan Baru in the Central Bangka Regency. 42 teachers from SMP Negeri 1 Pangkalan Baru in Central Bangka Regency made up the sample size. The respondents were all instructors at SMP Negeri 1 Pangkalan Baru in Central Bangka Regency, and the sampling method used was saturated sampling. 90 statement items were measured by distributing questionnaires using a 5-point Likert scale to collect the data. Multiple linear regression analysis is the method utilized for analysis. The study’s findings demonstrate that the leadership of the principal and the function of the school committee both significantly impact teacher effectiveness. Second, teacher performance is significantly and partially influenced by the principal’s leadership. Teacher performance is affected in part and significantly by the three responsibilities of the school committee.